Prevalence and risk factors associated with SARS-CoV-2 infections among veterinary practitioners and dogs patients, June-August 2020, Lagos, Nigeria - Folajimi O. Shorunke; Emmanuel C. Okolocha; Grace S. Kia; Aishat Usman; Oluseyi Akano; Emmanuel J. Awosanya (One Health Outlook, 2022)
Abstract Background Lagos State is the epicenter of COVID-19 in Nigeria, having the highest number of cases and death. Veterinary practitioners play an important role in public health and risk exposure to SARS-CoV-2, the virus that causes COVID-19 while attending to animal patients and owners. We determined the prevalence of covid-19 among veterinary practitioners and their dog patients in Lagos, and the associated risk factors during the lockdown. Methods We administered questionnaires, reviewed clinical records and conducted serological test to determine the COVID-19 status of 112 veterinary practitioners and 154 dog patients and to assess the associated factors in nine veterinary clinics or hospitals between June to August 2020. Data were analyzed using descriptive statistics, bivariate and multivariate analyses at 5% significant level. Result The mean age of participants was 37.5±10.5 and 66 (58.9%) were male. COVID-19 cases among the veterinary practitioners and dogs were 29 (25.9%) and 3 (2%), respectively. Predictors of COVID-19 cases among veterinary practitioners were contact with a SARS-CoV-2 infected dog (AOR: 25.42; CI 4.73-136.66); being a veterinary doctor working during the lockdown (AOR: 6.11; CI 1.56-24.00) and not disinfecting examination table after attending to dogs (AOR: 12.43; CI 1.39-110.99). Conclusion Veterinary practitioners and dogs in Lagos were exposed to SARS-COV-2 virus during the COVID-19 lockdown. Contact with SARS-CoV-2 infected dogs, being a veterinary doctor working during the lockdown and not disinfecting examination tables after clinical examination were predictors of COVID-19 cases among veterinary practitioners in Lagos State. Strict Infection, Prevention and Control measures are recommended in veterinary practice.